Fiscal Stimulus and Households' Non-Durable Consumption Expenditures: Evidence from the 2009 Australian Nation Building and Jobs Plan - Emma Aisbett; Markus Brueckner; Ralf Steinhauser (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In 2009 the Australian government delivered 8 billion in direct payments to households. These payments were pre-announced and randomly allocated over a 5-week period. We exploit this random allocation to estimate the causal response of households consumption expenditures. While we don't find a effect on consumption expenditures at the time of transfer we find a small, albeit statistically significant increase in consumption expenditures at the time of the announcement of the fiscal stimulus.
Keywords: E62; 330